Assessment of SARS-CoV-2 surrogate inactivation on surfaces and in air using UV and blue light-based intervention technologies. (4th March 2023) - Singh, Dilpreet; Soorneedi, Anand R.; Vaze, Nachiket; Domitrovic, Ron; Sharp, Frank; Lindsey, Douglas; Rohr, Annette; Moore, Matthew D.; Koutrakis, Petros; Nardell, Ed; Demokritou, Philip
ABSTRACT: The COVID-19 pandemic has created an urgent need to utilize existing and develop new intervention technologies for SARS-CoV-2 inactivation on surfaces and in the air. Ultraviolet (UV) technology has been shown to be an effective antimicrobial intervention. Here a study was conducted to determine the efficacy of commercially available UV and blue light-based devices for inactivating HCoV-229E, a surrogate of SARS-CoV-2. The results indicate that two UV devices designed for surface disinfection, with doses of 8.07 µJ/cm 2 for the 254 nm device and 20.61 µJ/cm 2 for the 275 nm device, were efficient in inactivating 4.94 logs of surface inoculated HCoV-229E. Additionally, a 222 nm UV device with intended ceiling-based operation was effective in inactivating 1.7 logs of the virus inoculated on surface, with a dose of 6 mJ/cm 2 . A ceiling-based device designed to emit blue light at 405 nm was found to produce 89% reduction in HCoV-229E inoculated on a surface for a dose of 78 J/cm 2 . Finally, the UV based 222 nm device was found to produce a 90% reduction in the concentration of airborne HCoV-229E, at a 55 µJ/cm 2 dose. These results are indicative of the great potential of using UV based technology for the control of SARS-CoV-2. Implications : An important avenue of arresting COVID-19 and future pandemics caused by infectious pathogens is through environmental disinfection. To this effect, the study presented here evaluates commercially available UV and blue light based antimicrobial devices for their ability to kill the human coronavirus HCoV-229E, a surrogate of SARS-CoV-2, on surfaces and in air. The results indicate that two handheld UV devices produced complete inactivation of surface viral inoculum and a UVC ceiling based device produced 1 log reduction in HCoV-229E in air. These results imply the efficacy of UV technology as an antimicrobial tool, especially for rapid disinfection of indoor air.